Caracterización del emprendimiento de las mujeres de la provincia de Virú - Velasquez Alva, Maria Elena (2019)
ABSTRACT The purpose of the research is to obtain information on the characteristics of women entrepreneurs in the province of Virú -La Libertad-Peru in order to identify their demographic data; your educational, work and family background; also their administrative / managerial skills, the nature of the enterprises and factors that motivated them to become entrepreneurs, overcoming various obstacles. To do this, a survey was conducted applying a questionnaire to the totality of the sample universe, made up of 163 women with ventures. The results show that they do not constitute a homogeneous group since it is evident that their antecedents in educational level prior to the work they are currently carrying out, is not related to the nature of their undertakings: most of them have no previous experience. On the other hand, their family history does influence them because they participated, in general, in independent activities. They involve their relatives as partners or employees evidencing a protection of the role of women in the family. As for the administrative and managerial, its management is based on successes and errors. Expressions of achievement and autonomy are more frequent factors than economic circumstances to stimulate women's entrepreneurship.